Humbo Ethiopia assisted natural regeneration project - Biryahwaho, B.; Misiko, Michael T.; Tefera, H.; Tofu, A. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2012)
Case study for the report "Institutional innovations in African smallholder carbon projects" available at http://hdl.handle.net/10568/21222